Young adults’ job satisfaction in Poland and the Czech Republic: a comparative analysis - Szulc-Obłoza, Agnieszka; Osińska, Magdalena; Śliwicki, Dominik; Szczepaniak, Małgorzata (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: Job satisfaction as an attitude that reflects an evaluation judgment of the various aspects of a job is an essential factor influencing employees as well as employers. The well-being of individuals, activity in the labor market, productivity, and turnover are examples of effects of job satisfaction. The inclusion of the circumstances of Poland and the Czech Republic countries and additionally young generations (GenY and GenZ) context enables the formulation of practical implications for increasing job satisfaction for both employers and employees in CEE countries. Aim: The research aims to identify factors that shape job satisfaction patterns among young adults, including age as an indicator variable in Poland and the Czech Republic. The identification is based on the two separate ordered logit models estimated in the group of young adults ages 18–29. The models were built upon the data collected in 2021 in a survey using the CAWI technique on a sample of 304 respondents in Poland and 259 in the Czech Republic. Result: The results of the logit models estimation indicate that job satisfaction in Poland and the Czech Republic is determined by various sets of factors considered in four dimensions, i.e., behavioral, economic, educational, and socio-demographic. Substantial differences between young adults in both countries were recognized. The greatest impact on job satisfaction in Poland has the willingness to control expenses and wage satisfaction. In the Czech Republic, job satisfaction is most strongly influenced by the imposition of rules that discipline expenditure and wage satisfaction.